Differences in Self-Regulated Learning Strategies Between Students Who Follow Organizations and Do Not Follow Organizations - Sitorus, Erics Boy Harapan; Rosito, Asina Christina (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
The purpose of this study was to look at the differences in self-regulated learning (SRL) strategies for students who join and do not join organizations in Universitas HKBP Nommensen (UHN). The hypothesis in this study is that there are differences in SRL strategies between students who join organizations and students who do not join organizations. This study used quantitative approach, with research subjects consisting of 130 students who join the organization and 130 students who do not join the organization. The instrument used in this study is the SRL strategy scale. Based on hypothesis testing using the independent t-test, it was found that there were significant differences in SRL strategies between students who join organizations and those who do not join organizations (t = 2.63, p <0.05) in which students who join organizations were significantly higher in using SRL strategies compared to students who do not join the organizations. Based on the results of this study, it can be concluded that active involvement in the organization provides self-regulation training experiences for students so that the use of SRL strategies is higher in the learning process.Tujuan dari penelitian ini adalah dalam melihat perbedaan strategi self-regulated learning (SRL) pada mahasiswa yang mengikuti organisasi dan tidak mengikuti kegiatan organisasi di Universitas HKBP Nommensen (UHN). Hipotesis yang diajukan dalam penelitian ini adalah terdapat perbedaan dalam strategi SRL antara mahasiswa yang mengikuti organisasi dan mahasiswa yang tidak mengikuti organisasi. Penelitian ini menggunakan metode penelitian kuantitatif, dengan subjek penelitian yang terdiri dari 130 mahasiswa yang mengikuti organisasi dan 130 mahasiswa yang tidak mengikuti organisasi. Instrument pengumpulan data menggunakan skala strategi SRL dari teori Zimmerman (1898). Berdasarkan pengujian hipotesis dengan menggunakan independent t-test diperoleh hasil bahwa terdapat perbedaan signifikan dalam strategi SRL antara mahasiswa yang mengikuti organisasi dan yang tidak mengikuti organisasi (t = 2.63, p < 0.05) dimana mahasiswa yang mengikuti organisasi lebih tinggi secara signifikan dalam menggunakan strategi SRL dibandingkan dengan mahasiswa yang tidak mengikuti organisasi. Berdasarkan hasil penelitian ini, dapat disimpulkan bahwa keterlibatan aktif dalam organisasi memberikan pengalaman latihan pengaturan diri bagi mahasiswa sehingga penggunaan strategi SRL semakin tinggi dalam proses pembelajarannya.